Accessibility of the Poor to the Rural Water Supply 1980 - Planning Commission (Planning Commission, 1980)
Until the Third Five Year Plan (1961-66) drinking water supply formed an important component of the amenities scheme under the Community Development Programme. The National Water Supply and Sanitation Programme of the Ministry of Health undertaken in 1954 also aimed to provide drinking water and sanitation facilities to both rural and urban areas. During the Fourth Plan (1969-74), the emphasis was shifted to the areas of acute scarcity and those endemic to water-borne diseases for which 64 per cent of the provision under Rural Water Supply was assigned. In the meanwhile, Centrally Sponsored Scheme known as the ‘Accelerated Rural Water Supply’ (ARP) was introduced in 1972-73. This was with the main objective of providing drinking water in the difficult areas and ‘problem villages’ (1.53 lakhs) as identified by the Assessment Survey (1972) conducted at the instance of the Government of India.
A Quick Evaluation Study Programme Evaluation Organisation Planning Commission Government of India